Case Report: Severe Eosinophilic Asthma Associated With ANCA-Negative EGPA in a Young Adult Successfully Treated With Benralizumab - Ricciardi, Luisa; Soler, Daniel Griscti; Bennici, Alessandra; Brunetto, Silvia; Pioggia, Giovanni; Gangemi, Sebastiano (Frontiers in Pharmacology, 2022)
Abstract Background Traditionally, Eosinophilic Granulomatosis with Polyangiitis (EGPA) has been treated with systemic corticosteroids and immunosuppressants. In recent years, therapeutic efforts have been directed towards targeting eosinophils which represent a major player in the pathogenesis of EGPA. In 2017 the Food and Drug Administration (FDA) approved mepolizumab, a humanized monoclonal antibody targeting interleukin 5 (IL-5) which reduces the production and survival of eosinophils, already used to treat severe eosinophilic asthma, for the management of EGPA. Benralizumab is a humanized monoclonal antibody that targets the IL-5 receptor and is indicated in the treatment of severe eosinophilic asthma. Case description We describe the case of a young lady with a positive history of severe eosinophilic asthma associated with EGPA, treated successfully with benralizumab.